2007
DOI: 10.1158/0008-5472.can-06-4415
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Down-regulation of E-Cadherin with Squamous Cell Carcinoma Progression: Loss of E-Cadherin via a Prostaglandin E2-EP2–Dependent Posttranslational Mechanism

Abstract: The incidence of skin cancer is on the rise, with over 1 million new cases yearly. Although it is known that squamous cell cancers (SCC) are caused by UV light, the mechanism(s) involved remains poorly understood. In vitro studies with epithelial cells or reports examining malignant skin lesions suggest that loss of E-cadherin-mediated cell-cell contacts may contribute to SCCs. Other studies show a pivotal role for cyclooxygenase-dependent prostaglandin E 2 (PGE 2 ) synthesis in this process. Using chronically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 44 publications
8
77
0
Order By: Relevance
“…Recent work in cell culture has shown that chemical or antisense interference with the prostaglandin signaling pathway components results in decreased Snai1 transcription and increased E-cadherin protein levels (Dohadwala et al, 2006;Brouxhon et al, 2007). However, our qRT-PCR and whole-mount ISH analyses showed that snai1a and snai1b levels were not significantly different in ptges versus control morphants ( Fig.…”
Section: Snai1a Protein Expression Is Stabilized In the Presence Of Pmentioning
confidence: 58%
“…Recent work in cell culture has shown that chemical or antisense interference with the prostaglandin signaling pathway components results in decreased Snai1 transcription and increased E-cadherin protein levels (Dohadwala et al, 2006;Brouxhon et al, 2007). However, our qRT-PCR and whole-mount ISH analyses showed that snai1a and snai1b levels were not significantly different in ptges versus control morphants ( Fig.…”
Section: Snai1a Protein Expression Is Stabilized In the Presence Of Pmentioning
confidence: 58%
“…In the present study, several hundreds of genes showed changed expression in the tumor tissues from the EP2-knockout mice compared with tumor tissues from the wild-type mice. A reason for this could be that EP2 signaling in host tissues is involved in several different pathways that are important events in tumor cells associated with tumor progression, including angiogenesis, the upregulation of COX-2, the loss of E-cadherin expression and anti-apoptosis in stem cells (16,22,(25)(26)(27)(28). Prom-1, also known as CD133, and CD44 are well-known markers of cancer stem cells, indicating reduced gene expression in the tumor tissues from the EP2-knockout mice in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Mice bearing tumors, with an estimated volume of 100 mm 3 were subsequently randomized to receive a one-time injection of saline (n ¼ 6), IgG (10 mg/kg, n ¼ 6), or anti-sEcad mAb (10 mg/kg, n ¼ 7) and tumor growth was monitored for an additional 20 days. Starting from 12 days, anti-sEcad treatment demonstrated a significant decrease in tumor volume and burden compared with controls ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the best known function of PTEN involves the dephosphorylation of PtdIns (3,4,5)P3 at the plasma membrane surface, cytoplasmic PTEN has been shown to inhibit cell proliferation (38). Moreover, nuclear PTEN has been proposed to regulate the cell cycle through the suppression of cyclin D1 activity (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation